Conceptualizing Learning Environments in the Health Professions - Gruppen, Larry D; Irby, David M; Durning, Steven J; Maggio, Lauren A (Academic medicine, 2019)
The learning environment (LE) is an important and frequently discussed topic in the health professions education literature. However, there is considerable inconsistency in how the LE is defined and described. The authors propose a definition of the LE and a conceptual framework to facilitate health professions educators in understanding, studying, and designing interventions to improve the LE. To arrive at this conceptual framework, the authors employed a living systems perspective that draws on various frameworks and theories, including ecological psychology, workplace learning, situated cognition, and sociomateriality theory. The conceptual framework identifies five overlapping and interactive core components that form two dimensions: the psychosocial dimension and material dimension. The psychosocial dimension comprises three components: the personal, social, and organizational. Intertwined with the psychosocial dimension at each level is the material dimension, which encompasses physical and virtual spaces. This theoretical lens can facilitate identifying and analyzing problems in the LE and guide development of interventions to mitigate them. The authors conclude with several practical suggestions for health professions educators, investigators, and editors.